First autochthonous case of clinical Hepatozoon felis infection in a domestic cat in Central Europe. (October 2019) - Basso, Walter; Görner, Dagmar; Globokar, Majda; Keidel, Anke; Pantchev, Nikola
Abstract: Three different Hepatozoon (Apicomplexa, Hepatozoidae) species have been described infecting domestic cats in Europe (i.e. H. felis, H. canis and H. silvestris ), however, reports on clinical hepatozoonosis are uncommon and treatment protocols are not clearly defined. A six-year-old male European short-hair cat from Austria presented poor general condition, lethargy, anorexia, icterus, a painful abdomen, fever, ruffled hair and a tick infestation, and it had never left Austria. Laboratory tests revealed leukopenia, thrombocytopenia and increased serum levels of symmetric dimethylarginine (SDMA) and bilirubin. In May Grünwald-Giemsa-stained blood smears, structures resembling Hepatozoon gamonts were observed inside neutrophil granulocytes. A PCR targeting a fragment of the 18S rRNA gene of Hepatozoon spp. and DNA sequencing allowed the diagnosis of H. felis -DNA in blood samples. The cat was treated with imidocarb dipropionate (6 mg/kg body weight, repeated after 14 days) and doxycycline monohydrate (5 mg/kg body weight twice a day, p.o., for four weeks) and recovered completely. A broad haematological and biochemical laboratory control after six months showed all evaluated parameters under normal ranges. Coinfection with other feline pathogens (i.e. feline leukaemia virus, feline immunodeficiency virus, feline Coronavirus, Leishmania and Dirofilaria immitis ) could not be detected . This study reveals the presence of H. felis in Austria and provides more evidence on the geographical distribution and pathogenicity of this parasite for domestic cats. To the authors' knowledge, this is the first autochthonous case of feline hepatozoonosis in Central Europe. Graphical abstract: Unlabelled Image Highlights: Clinical Hepatozoon felis infection in a domestic cat was diagnosed in Austria. The diagnosis was achieved by microscopy of blood smears, PCR and DNA-sequencing. Possible coinfections with other feline pathogens were ruled-out . The cat recovered completely after treatment with imidocarb and doxycycline. This represents the first autochthonous case of feline hepatozoonosis in Central Europe.